Structural and mechanistic insights into the cleavage of clustered O-glycan patches-containing glycoproteins by mucinases of the human gut - Taleb, Víctor; Liao, Qinghua; Narimatsu, Yoshiki; García-García, Ana; Compañón, Ismael; Borges, Rafael Junqueira [UNESP]; González-Ramírez, Andrés Manuel; Corzana, Francisco; Clausen, Henrik; Rovira, Carme; Hurtado-Guerrero, Ramon (Springer Nature, 2022)
Mucinases of human gut bacteria cleave peptide bonds in mucins strictly depending on the presence of neighboring O-glycans. The Akkermansia muciniphila AM0627 mucinase cleaves specifically in between contiguous (bis) O-glycans of defined truncated structures, suggesting that this enzyme may recognize clustered O-glycan patches. Here, we report the structure and molecular mechanism of AM0627 in complex with a glycopeptide containing a bis-T (Galβ1-3GalNAcα1-O-Ser/Thr) O-glycan, revealing that AM0627 recognizes both the sugar moieties and the peptide sequence. AM0627 exhibits preference for bis-T over bis-Tn (GalNAcα1-O-Ser/Thr) O-glycopeptide substrates, with the first GalNAc residue being essential for cleavage. AM0627 follows a mechanism relying on a nucleophilic water molecule and a catalytic base Glu residue. Structural comparison among mucinases identifies a conserved Tyr engaged in sugar-π interactions in both AM0627 and the Bacteroides thetaiotaomicron BT4244 mucinase as responsible for the common activity of these two mucinases with bis-T/Tn substrates. Our work illustrates how mucinases through tremendous flexibility adapt to the diversity in distribution and patterns of O-glycans on mucins.